Adam - Schrag, Ariel (Mariner Books, 2014)
"When Adam Freedman--a skinny, immature, and lackluster high school student from Piedmont, California--is sent by his parents to join his older sister Casey in New York City, he is hopeful that his life is about to change. And it sure does. It is the Summer of 2006--the year of gay marriage demonstrations and the rise of transgender rights--and Casey has thrust herself into New York's fringe lesbian, sexual, and political scene. Accustomed to being a social misfit, Adam now finds himself part of a wild subculture complete with underground clubs, drinking, and friendly women who take a surprisingly intense interest in him. It takes some time for him to realize many in this new crowd assume he is transgendered--a boy who was born a girl--or else why would he always be around? But then he meets Gillian, the girl of his dreams. If only she weren't a lesbian! And if only she didn't believe he was really (sort of) a girl. Ariel Schrag's scathingly funny and poignant debut novel puts a fresh spin on questions of love, attraction, self-definition, and what it takes to be at home in your own skin"--